Safety and Effectiveness of Naltrexone-Bupropion in Korean Adults with Obesity: Post-Marketing Surveillance Study - Lyu YS; Ahn H; Hong S; Park CY (Dove Medical Press, 2024)
Young Sang Lyu,1 Hongyup Ahn,2 Sangmo Hong,3 Cheol-Young Park4 1Division of Endocrinology and Metabolism, Department of Internal Medicine, Chosun University Hospital, Gwangju, Republic of Korea; 2Department of Statistics, Dongguk University, Seoul, Republic of Korea; 3Department of Internal Medicine, Hanyang University Guri Hospital, Hanyang University College of Medicine, Guri, Republic of Korea; 4Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, Seoul, Republic of KoreaCorrespondence: Cheol-Young Park, Division of Endocrinology and Metabolism, Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, 29 Saemunan-ro,Jongno-gu, Seoul, 03181, Republic of Korea, Email cydoctor@skku.eduPurpose: To investigate the safety and effectiveness of naltrexone-bupropion in Korean adults with obesity.Patients and methods: This was a prospective, observational multicenter study from April 29, 2016, to April 28, 2022. Individuals with obesity with a body mass index of ≥ 30 kg/m2 or ≥ 27 kg/m2 who had obesity-related comorbidities were included. The naltrexone-bupropion dose was gradually titrated weekly from 8/90 to 32/360 mg and maintained at the maximum tolerated dose. In total, 612 and 300 individuals were evaluated for safety and effectiveness, respectively.Results: In total, 41.34% individuals reported drug-related adverse reactions, such as nausea (19.12%), headache (7.68%), and dizziness (5.23%). Older age and comorbidities were significantly associated with adverse events. At 12 weeks after reaching the maintenance dose, naltrexone-bupropion 32/360 mg resulted in the greatest weight reduction (− 7.21%) compared with other doses, which persisted at week 24 (− 7.69%). The naltrexone-bupropion 16/180 mg resulted in significant weight reduction, achieving − 5.99% and − 9.18% reductions at weeks 12 and 24, similar to that with naltrexone-bupropion 32/360 mg. Young age and no comorbidities were significantly associated > 5% weight reduction.Conclusion: Naltrexone-bupropion demonstrated marked stability and weight loss effectiveness, particularly in young individuals with obesity without comorbidities. Therefore, individualized treatment is necessary when prescribing naltrexone-bupropion.Keywords: naltrexone-bupropion, obesity management, post-marketing survey, weight loss efficacy, adverse events